Advances in research on the role of neutrophils in organ transplant rejection - Yu, Shaochen; Zhang, Mengjie; Dou, Ziyue; Tian, Beibei; Lu, Jian (Frontiers in Immunology, 2025)
Organ transplantation is an effective treatment for end-stage organ failure, but rejection remains a major obstacle to transplant success. Neutrophils play a key role in organ transplant rejection, participating not only in early immune responses but also exacerbating graft injury through mechanisms such as the release of neutrophil extracellular traps (NETs). Therefore, in-depth exploration of the immunological role of neutrophils in transplant rejection and their interactions with other immune cells is highly important. This article reviews the latest research progress on the mechanisms of action of neutrophils in transplant rejection and their impact on grafts while also assessing the clinical application prospects of immunosuppressive strategies targeting neutrophils and NETs. By integrating current basic and clinical research findings, this article aims to provide theoretical support and new research directions for the diagnosis and treatment of neutrophil-related rejection, with the goal of improving organ transplant success rates and patient quality of life.